2017
DOI: 10.18632/oncotarget.16019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metformin on C-reactive protein levels in women with polycystic ovary syndrome: a meta-analysis

Abstract: The impact of the recommended first-line treatment with metformin on C-reactive protein (CRP) levels in patients with polycystic ovary syndrome (PCOS) is still controversial. We conducted a meta-analysis of studies reporting the impact of metformin on serum CRP levels in women with PCOS. The weighted mean differences (WMDs) and the corresponding 95% confidence intervals (CIs) were used to assesse the effects. GRADE approach was used to assesse the quality of the evidence. A total of 20 studies that included 43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
5
1
Order By: Relevance
“…In the present study, subgroup analyses indicated that there was no significant effect of dose of metformin (<2000 and ≥2000 mg/d) on the levels of CRP, TNF-α, and IL-6 in patients with T2D. In contrast to our findings, the evidence from Chen et al 39 showed decreased CRP levels in the subgroup with a dose of <2000 mg/d compared with the ≥2000-mg/d subgroup. Lin et al 40 demonstrated that addition of 1500 mg metformin daily for 3 months lowered the levels of IL-6 in women with polycystic ovary syndrome (PCOS).…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, subgroup analyses indicated that there was no significant effect of dose of metformin (<2000 and ≥2000 mg/d) on the levels of CRP, TNF-α, and IL-6 in patients with T2D. In contrast to our findings, the evidence from Chen et al 39 showed decreased CRP levels in the subgroup with a dose of <2000 mg/d compared with the ≥2000-mg/d subgroup. Lin et al 40 demonstrated that addition of 1500 mg metformin daily for 3 months lowered the levels of IL-6 in women with polycystic ovary syndrome (PCOS).…”
Section: Discussioncontrasting
confidence: 99%
“…In consistent with a study, it proved that higher dose metformin may be more efficient for BMI reduction in women with PCOS. [ 45 ] However, Chen et al [ 46 ] observed that CRP levels decreased more in the subgroup with a dose of <2000 mg/day than that of ≥2000 mg/day. The explanation could be that BMI, age, and clinical phenotypes influence the effect of metformin in PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted with large sample size, metformin reduced CRP level after 24 weeks, but the mechanism of its action was not accurately determined (4,27). In a meta-analysis carried out on 20 studies involving 433 women with polycystic ovary syndrome, the decreasing effect of metformin on CRP plasma levels, especially in obese women, was confirmed (28). In another meta-analysis conducted on 216 studies, it was found that metformin significantly reduced CRP in women with polycystic ovary syndrome, but it did not significantly affect the IL-6 (29).…”
Section: Metformin and Inflammatory Markersmentioning
confidence: 97%